The Women's Leadership in Private University Governance in Gorontalo Province - Thalib, Tety; Aneta, Asna; Abdussamad, Juriko (Iapa Proceedings Conference, 2024)
This study aims to explore women's leadership in the context of private higher education governance (PTS) in Gorontalo Province. Through a qualitative approach, this study analyzes the factors that influence leadership styles, including masculine and feminist leadership styles, as well as the challenges and obstacles faced in managing educational institutions.The results show that female leaders tend to adopt a democratic and collaborative leadership style, listen to input from team members, and create an inclusive work environment. Despite obstacles related to a centralized management system, leaders can still implement strategies that build synergy and collaboration among team members. This study identifies supporting factors such as foundation support, strategic campus locations, and innovative team commitment as key elements in improving the quality of education management.The implications of these findings indicate the importance of integrating masculine and feminist leadership styles to achieve organizational success. The recommendations produced aim to maximize the effectiveness of women's leadership in the context of PTS, as well as encourage the development of more inclusive and collaborative policies in the management of higher education in Gorontalo Province. This research is expected to make a significant contribution to improving the quality of education and women's empowerment in the realm of higher education leadership.